Digital Financial Literacy Training for MSME Operators in Tapak Gedung Village Kabawetan District Kepahiang Regency - Fitranita, Vika; Sriwidharmanely, Sriwidharmanely; Hatta, Madani; Suniga, John Paul C. (CV Media Inti Teknologi, 2025)
This activity aims to improve digital financial literacy in MSMEs in Tapak Gedung Village through training and mentoring programs. This activity is motivated by the low level of digital financial literacy in Indonesia, especially for Micro, Small and Medium Enterprises (MSMEs). The 2022 National Survey on Financial Literacy and Inclusion (SNLIK) conducted by the Financial Services Authority (OJK) shows that financial literacy in Indonesia has only reached 49.68%, while financial inclusion is at 85.10%. This gap indicates that although many people have access to digital financial services, their understanding is still limited, making them vulnerable to illegal investments and online scams. The methods used in this activity include socializing the importance of digital finance, providing hands-on training on using financial applications such as Paper.id and providing ongoing mentoring to support implementation. An evaluation was conducted after the training to measure participants' understanding and application of the knowledge gained. The results showed that participants showed an increased understanding in using digital financial applications, especially in recording transactions, managing cash flow, and real-time financial reporting. In addition, MSME players also began to realize the importance of investing in legal financial institutions registered and supervised by OJK. In conclusion, digital financial literacy training has a positive impact on the financial management skills of MSMEs. With increased knowledge, small business owners can manage their businesses with more confidence, improve competitiveness, and navigate the challenges of the digital economy more effectively.